2018
DOI: 10.3138/cpp.2018-014
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Under-Claiming of Compensable Workplace Injuries in Alberta, Canada

Abstract: This study confirms and refines prior estimates of under-claiming of workers’ compensation benefits and suggests that under-claiming negatively affects the utility of workers’ compensation data in injury prevention efforts. A 2017 online poll ( N = 2,000) queried the injury and workers’ compensation experiences of Alberta workers. Approximately 21.5 percent of respondents reported at least one work-related injury in the previous 12 months, of which 41.8 percent were disabling injuries. Only 31 percent of worke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…While some employers did not provide any OHS training, the OHS training that others provided often did not meet the specific needs of the participants in this study. These findings agree with conclusions reached in other research that found a low level of compliance with basic OHS obligations in Alberta′s employers [ 42 ].…”
Section: Discussionsupporting
confidence: 93%
“…While some employers did not provide any OHS training, the OHS training that others provided often did not meet the specific needs of the participants in this study. These findings agree with conclusions reached in other research that found a low level of compliance with basic OHS obligations in Alberta′s employers [ 42 ].…”
Section: Discussionsupporting
confidence: 93%
“…Alberta makes reporting such injuries administratively easy. Yet, prior analysis of this data set found that 69.1% of serious injuries are not reported to the WCB (Barnetson et al, 2018). We queried why nonreporters did not file a claim with the WCB and the results are summarized in Table 4.…”
Section: Why Workers Don't Report and Refusementioning
confidence: 99%
“…Complaintand claims-based enforcement of employment rights assumes workers are willing and able to pursue their rights. Prior research has revealed that there is a significant level of under-claiming of benefits for workplace injuries (Barnetson, Foster, & Matsunaga-Turnbull, 2018;Shannon & Lowe, 2002). This study examines fear of retaliation as a potential explanation for workers' reluctance to exercise various statutory employment rights by establishing baseline levels of worker fear levels around exercising 14 employment rights.…”
Section: Introductionmentioning
confidence: 99%
“…The under‐utilization of the compensation system has important consequences that have been explored in the published literature. Under‐reporting transfers the cost of workplace injury: (a) to workers when they are not paid for time off; (b) to employers when they choose to pay employees for time off work; (c) to employee benefit plans; (d) to the health‐care system 6 . Under‐reporting workplace injuries may also lead to misplaced complacency, and thwart opportunities for workplace and policy improvements, 6 and, when compensation claims are used as a key metric, results in an inaccurate assessment of the burden of injury across labor market groups.…”
Section: Introductionmentioning
confidence: 99%
“…Under‐reporting transfers the cost of workplace injury: (a) to workers when they are not paid for time off; (b) to employers when they choose to pay employees for time off work; (c) to employee benefit plans; (d) to the health‐care system 6 . Under‐reporting workplace injuries may also lead to misplaced complacency, and thwart opportunities for workplace and policy improvements, 6 and, when compensation claims are used as a key metric, results in an inaccurate assessment of the burden of injury across labor market groups. Because most of Canada's workers are covered under the system, if some subgroups are less likely to claim their injuries to compensation, concrete steps should be taken to identify and remove barriers to reporting.…”
Section: Introductionmentioning
confidence: 99%